2001
DOI: 10.1103/physrevlett.87.054504
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Dependent Boundary Slip in an Aqueous Newtonian Liquid

Abstract: We report direct measurements of hydrodynamic drainage forces, which show clear evidence of boundary slip in a Newtonian liquid. The degree of boundary slip is found to be a function of the liquid viscosity and the shear rate, as characterized by the slip length, and is up to approximately 20 nm. This has implications for confined biological systems, the permeability of microporous media, and for the lubrication of nanomachines, and will be important in the microcontrol of liquid flow. We also show that curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
431
5
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(465 citation statements)
references
References 32 publications
21
431
5
8
Order By: Relevance
“…The conclusions have been confirmed by Molecular Dynamics simulations [135] and are consistent with studies of flow in capillaries with diameters of tens of nanometers [3,91]. In this context, the large number of recent published experiments reporting some form of (apparent) slip with λ ∼ 1 nm−1 µm in the flow of Newtonian liquids is surprising [9,16,17,18,29,30,32,33,38,39,40,67,87,88,68,108,116,125,126,150,162,163,178,192,193,194,195], and has allowed to re-discover a few early [29] Poly(carbonate)+PVP SDS solutions studies reporting some degree of slip [21,34,46,141,160]. In part, this chapter is an attempt to describe and interpret these more recent experimental results.…”
Section: Newtonian Liquids: No-slip? Slip?supporting
confidence: 76%
See 1 more Smart Citation
“…The conclusions have been confirmed by Molecular Dynamics simulations [135] and are consistent with studies of flow in capillaries with diameters of tens of nanometers [3,91]. In this context, the large number of recent published experiments reporting some form of (apparent) slip with λ ∼ 1 nm−1 µm in the flow of Newtonian liquids is surprising [9,16,17,18,29,30,32,33,38,39,40,67,87,88,68,108,116,125,126,150,162,163,178,192,193,194,195], and has allowed to re-discover a few early [29] Poly(carbonate)+PVP SDS solutions studies reporting some degree of slip [21,34,46,141,160]. In part, this chapter is an attempt to describe and interpret these more recent experimental results.…”
Section: Newtonian Liquids: No-slip? Slip?supporting
confidence: 76%
“…Other more complex behaviors remain to be understood, including dependence of the results on the molecular shape and size [30,55,68,195], probe size [108], or viscosity [40,116]. The development of alternative direct experimental methods would allow for a more precise quantification of slip phenomena.…”
Section: Perspectivementioning
confidence: 99%
“…For strong liquid-wall interactions AFM results indicate that also slip occurs. Significant slip lengths of up to 20 nm were found by Craig et al in aqueous sucrose solutions (viscosities of 0.01-0.08 Pa s) [1031]. They measured hydrodynamic forces between gold coated silica spheres and gold coated mica.…”
Section: Methodsmentioning
confidence: 94%
“…Over the last few years, a number of pressure-driven flow [7,8,9,10], shear-flow [11], and squeeze-flow experiments [12,13,14,15,16,17,18] showing a response interpretable as some degree of slip for partially wetting liquids have been reported. Molecular dynamics simulations of Lennard-Jones liquids have also shown that slip can occur, but only at unrealistically high shear rates [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The first consists in performing indirect measurements, such as pressure-drop versus flow rate or squeezing rate versus resistance, and then use such measurements to infer a slip length. This procedure is indirect in the sense that it assumes that the flow resembles (2) and then equation (3), or an equivalent, is used to determine λ [7,8,10,12,13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%